Students’ perception of the educational environment in a Medical Faculty with an innovative curriculum in Sri Lanka - Lokuhetty, M.D.S.; Warnakulasuriya, Sachini P.; Perera, Ranawakaarachchige I.R.; De Silva, Heethaka T.R.; Wijesinghe, Harshima D. (South‐East Asian Journal of Medical Education, Vol. 4 no. 1, 2010, 2010)
Introduction: The educational environment is crucial in determining the success of undergraduate medical education. The Dundee Ready Education Environment Measure (DREEM) is a validated tool to assess the educational environment created in medical schools. The University of Colombo, Faculty of Medicine (UCFM) is an established medical school with an innovative curriculum. Though the curriculum is periodically monitored the ‘educational environment’ crucial to its success is not regularly assessed. We studied the educational environment created at the UCFM, using the DREEM questionnaire. Materials and methods: The DREEM questionnaire was administered to a batch of 192 senior medical undergraduates at UCFM maintaining anonymity. The results were analysed using SPSS 16 and relevant statistical tests. Results were compared with relevant similar studies. Results: Of the 151 students (78.6%) who responded, majority (65.6%) responded ‘more positively than negatively’ to the DREEM inventory. The global mean score was 53.7% in comparison to medical schools of Dundee (69.5%), Nepal (65%) and Sri Jayawardenapura in Sri Lanka (53.6%). The study subscale scores were placed a step below the ideal score, similar to scores of above medical schools. Of the sub scales, the student’s perception of teachers and their perception of the atmosphere scored comparatively lower, with significant gender differences in perception. Discussion: Majority had a positive perception of the UCFM educational environment with males requiring more support in certain areas. The two Sri Lankan medical schools had similar results. Problem areas and areas requiring enhancement in the UCFM educational environment needs effective management for the success of its curriculum.